Self-medication among Alexandria University students and effect of an educational intervention on their self-medication knowledge, attitudes and practices - Hanafy, Sara A.; Gad, Zahira M.; El Bourgy, Mohamed D.; Wahdan, Iman H. (International Journal Of Community Medicine And Public Health, 2020)
Background: Self-medication (SM) among university students is a growing prevalent public health concern worldwide. It is highly prevalent in developing countries. SM leads to serious consequences such as drug misuse/abuse and adverse drug reactions. The study aims to determine the prevalence of SM among university students in Alexandria, Egypt and to assess the effect of an educational intervention on their SM knowledge, attitudes and self-reported practices (KAP). Methods: The study was conducted among 400 students using a cross sectional approach followed by one group pre/post-test intervention approach. Data were collected using an interviewing questionnaire. A health education program was designed and implemented among students then KAP were reassessed using the same questionnaire. Results: The prevalence of SM was estimated to be 79.5% among Alexandria University students. About one quarter (24.5%) of students had poor level of knowledge about SM and 47.5% had positive attitude towards SM. Logistic regression analysis revealed that father’s occupation as clerical, family member working as healthcare professional, medication sharing practice, and total SM knowledge score were the significant independent factors that affected SM. There were significant differences between pre and post intervention KAP scores. Conclusions: The prevalence of SM is high among university students. There is a significant effect of the intervention program on KAP about SM.